Tanda-tanda Bahaya Pada Ibu Hamil Trisemester III - iDA HAYATI (Pengabdian Masyarakat, 2021)
Abstract: Several study have shown that pregnancy has potential and risk for the mother. The world Health of Organisation (WHO) of all 15% of physiological pregnant women can develop complications in their pregnancy that can threaten their lives. 90% of maternal mortality during pregnancy is due to obstretric difficulties, in which the syringe is not predicated at the time of pregnancy. Therefore, midwives must handle as early as possible the danger sign in pregnant women that might occur. The purpos of this service is to increase the knowledge of pregnant women and their families in pregnancy complications of pregnancy. The method used is counseling pregnant women and families who visit the Segiri Community Health Center. Result Achievedd Pregnant women and their families understand the denger signs in pregnant women, especially in the third trimester and how to deal with them if they occur in pregnant women. Sugestions from community service activities need families' role and support in warning of denger signs in pregnant women.